The Dynamics of Teacher and Student Well-Being and Their Influence on Mathematics Well-Being: A Systematic Literature Review - Erlin Yuliana; Idat Muqodas; Juntika Nurihsan; Mubiar Agustin; Jelita Anastasia Simbolon; Gerawati Krismonika (Jurnal Pendidikan Progresif, 2026)
Teacher and student well-being is increasingly regarded as an integral part of healthy and effective mathematics education. Although the concept of well-being in education has developed rapidly, the dynamic and mutually influential relationship between teacher and student well-being, and their synergistic effects on well-being in mathematics learning, remain relatively new areas of research.  This study aims to present a structured synthesis of the latest empirical evidence (2021–2025) regarding the dynamics of the reciprocal relationship between teacher and student well-being, and its contribution to the mathematics learning climate (Mathematics Well-Being). A systematic search was conducted across three databases ScienceDirect, ERIC, and Springer in accordance with the PRISMA 2020 protocol. The search string utilized Boolean operators with the following keywords: (“teacher well-being” OR “teaching well-being”) AND (“student well-being” OR “student wellbeing”) AND (“mathematics education” OR “math well-being” OR “mathematical well-being”). Following a stepwise screening process, 16 empirical articles met the inclusion criteria and were analyzed using thematic synthesis. The synthesis identified three main pathways of reciprocal relationships: emotional, social, and cognitive. Teacher well-being plays an active role in enhancing students’ emotional engagement, motivation, and positive attitudes towards mathematics. Conversely, student well-being enhances job satisfaction, teaching effectiveness, and professional fulfillment among teachers, forming a reciprocal and mutually reinforcing cycle between teacher and student well-being. This two-way relationship forms the foundation of integral mathematical well-being, namely a cohesive state of emotional, intellectual, and relational balance in mathematics learning. This review emphasizes the importance of an inclusive approach that integrates student and teacher well-being as interdependent variables in sustainable mathematics education. This approach not only supports academic success but also the resilience, motivation, and emotional well-being of both students and teachers. Keywords: mathematics well-being, student, teacher, well-being, systematic literature review.